Nefertiti, queen and pharaoh of Egypt : her life and afterlife - Dodson, Aidan, 1962- (The American University in Cairo Press, 2020)
During the last half of the fourteenth century BC, Egypt was perhaps at the height of its prosperity. It was against this background that the "Amarna Revolution" occurred. Throughout, its instigator, King Akhenaten, had at his side his Great Wife, Nefertiti. When a painted bust of the queen found at Amarna in 1912 was first revealed to the public in the 1920s, it soon became one of the great artistic icons of the world. Nefertiti's name and face are perhaps the best known of any royal woman of ancient Egypt and one of the best recognized figures of antiquity, but her image has come in many ways to overshadow the woman herself. 0Nefertiti's current world dominion as a cultural and artistic icon presents an interesting contrast with the way in which she was actively written out of history soon after her own death. This book explores what we can reconstruct of the life of the queen, tracing the way in which she and her image emerged in the wake of the first tentative decipherment of Egyptian hieroglyphs during the 1820s-1840s, and then took on the world over the next century and beyond. 0All indications are that her final fate was a tragic one, but although every effort was made to wipe out Nefertiti's memory after her death, modern archaeology has rescued the queen-pharaoh from obscurity and set her on the road to today's international status.